Prominent Jews: the Absence and Presence of Jews in Postwar Netherlands - de Haan, Ido (Historein, 2019)
One of the most striking aspects of the Jewish community in the Netherlands after 1945 is the small number of people that belong to it. Despite their striking absence in Dutch society, Dutch Jews are a highly visible group. There are many ways, places and moments in which Jews have played a prominent role in Dutch society, and there are many issues in public debates that concern Jews. This article aims to reflect on this prominence, for it is neither self-evident nor unproblematic. Is not the claim to some special Jewish contribution an excess of Jewish pride, or an overdrawn philosemitism, which sets Jews apart much in the same way as antisemitism does? Such questions can only be answered experimentally, by looking at what happens when we analyse the remarkable presence of Jews in Dutch society. Is there an overrepresentation of actual Jews or an overdetermination of Dutch culture by symbolic Jews? Is there a decisive influence, a specific Jewish colouring and obsessive probing of the limits of Jewish life in a post-Holocaust society or nothing conclusive at all?